Green-PVC with full recycled industrial waste and renewably sourced content. (20th August 2019) - Correa, Carlos Alberto; de Santi, Cristiano Ribeiro; Leclerc, André
Abstract: Polyvinyl Chloride (PVC) resins and their compounds are very versatile materials with applications ranging from flexible packaging to rigid building products, such as extruded pipes, profiles and injection moulded electrical/plumbing fittings. Nowadays, large amounts of industrial waste resulting from PVC processing must be handled in order to comply with enacted environmental and health hazards legislations concerning plastic waste disposal. Nonetheless, provided the waste contamination is controlled at its source, PVC waste is potentially recyclable and can be compounded with thermoplastic starches leading to reprocessed formulations with renewable content. These formulations can be reengineered onto injection moulded appliances within a closed-loop manufacturing framework. Starches can be gelatinized by heat, pressure and shearing with glycerol, and in the present work, a by-product of the biodiesel manufacturing was used for this purpose. The main aspects related to cascaded recycling of PVC waste from pipe processors are discussed, in regard to challenges for developing alternative green markets for plastic products in terms of recycling technology and properties compliance for using reprocessed plastic plumbing waste on electrical fittings. Coping with hygroscopic nature of glycerol plasticized starch was the main challenge and many bioderived plasticizers have been tested to overcome this drawback. The research on Green PVC implied that eco-innovation in the conventional plastic industry requires "drop-in" solution regardless of their renewably or fossil sourced feedstock. Furthermore, the green value is not clearly perceived as marketing advantage by plastic processors and consumers and a green-premium associated with production costs tend to hinder a pervading market. Graphical abstract: Image 1 Highlights: Identification of the main waste streams of PVC pipe and fittings industry in Brazil. Design of Green-PVC based on melt compounding of PVC waste with glycerol plasticized starch. Analysis of the Green-PVC approach as a closed-loop manufacturing framework. Examples of applications of injection moulded Green-PVC in electrical fittings. Evaluation of the Green-PVC approach within the circular economy perspective.